Exploring the Intersection of Faith and Mental Health in Religious Clients - Antoniou, Nikos; Kalogeropoulos, Dimitra (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective:  This study aims to explore the intersection of faith and mental health among religious clients, focusing on how spiritual beliefs influence mental health experiences, coping strategies, and help-seeking behaviors.Methods and Materials: A qualitative research design was employed, involving semi-structured interviews with 29 religious individuals from Greece. Participants were selected based on their self-identified religious affiliation and personal experiences with mental health. Data collection was conducted until theoretical saturation was reached, and NVivo software was used for data analysis. The study utilized thematic analysis to identify and interpret key themes related to the role of faith in mental health.Findings: The findings revealed that faith played a dual role in participants’ mental health experiences. Religious beliefs were a significant source of strength and resilience, with practices such as prayer, scripture reading, and community support serving as coping mechanisms. However, participants also reported tensions between religious beliefs and mental health care, particularly regarding stigma, spiritual interpretations of mental illness, and reluctance to seek professional help. Many participants expressed a desire for faith-sensitive mental health care that respects their spiritual needs. The study also highlighted the need for clergy to receive training in mental health awareness to reduce stigma and promote help-seeking behaviors.Conclusion: The study concludes that while faith can be a powerful resource for coping with mental health challenges, it can also create barriers to seeking professional care due to stigma and spiritual bypassing. Integrating faith-sensitive approaches in mental health care is essential for improving outcomes for religious clients, with recommendations for training clergy and enhancing faith-based mental health initiatives.